Spatial-temporal evolution of industrial land transformation effect in eastern China - Dai, Deyi; Yang, Jixin; Rao, Yingxue (Frontiers in Environmental Science, 2022)
The study of industrial land transformation effect is of great significance for promoting the sustainable and healthy development of the industrial economy. This paper adopts panel data of 10 provinces in eastern China from 2008 to 2020, constructs an indicator system including five dimensions on the premise of clarifying industrial land transformation and applies the comprehensive evaluation method of gray relational theory to measure its effect. The results show that: (1) overall, industrial land transformation effect in the eastern region shows a good development trend but there are gaps between different provinces, which have been expanding over time in the extreme values. (2) At the provincial level, in terms of industrial land transformation effect, Beijing, Shanghai, Guangdong and Jiangsu are in the leading positions; Zhejiang, Fujian and Hebei are in the middle positions; and Tianjin, Hainan and Shandong are slightly behind. (3) At the dimensional level, Industrial land development dimension and industrial land employment dimension generally show a good trend; the spatial pattern of industrial land optimization dimension and environmental pollution control dimension does not change significantly with most provinces at a low level; development conditions support dimension shows a positive spatial trend, indicating that each province attach importance to infrastructure construction and scientific technological progress, creating positive conditions for industrial land transformation. Overall, the results identify whether industrial land in eastern China is being used rationally, which has practical implications for promoting industrial structure upgrading, scientific and technological progress and ecological environment improvement.